The Influence of Teacher's Teaching Style on Learning Motivation of Grade 5 Elementary School Students: Pengaruh Gaya Mengajar Guru Terhadap Motivasi Belajar Siswa Kelas 5 Sekolah Dasar - Ferawati Firdaus; Nurdyansyah Nurdyansyah (Academia Open, 2022)
Teaching is an activity that has educational value. Educational values ​​color the interactions that occur between teachers and students. Motivation is the basic drive that moves a person to behave. This drive is in someone who moves him to do something according to the impulse in him. Teachers who can manage classes well so that they can motivate, provide teaching, and provide knowledge to students to equip students not only cognitively and psychomotorically but by prioritizing the affective or attitude or character of these students in the future as the nation's successors. The purpose of this study was to determine the effect of the teacher's teaching style on the learning motivation of the 5th grade MINU NGINGAS students. The form of this research is quantitative research, while the population members in this study are 5th grade students with a total of 94 students. The sample members in this study were 30 students who were randomly selected using the cluster random sampling technique. The data collection techniques used in the research are questionnaires as the main method, documentation as a supporting method.